2014
DOI: 10.1007/s40891-014-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress Transfer Mechanism in 2D and 3D Unit Cell Models for Stone Column Improved Ground

Abstract: Stone column has been used widely to improve the foundation for many structures. Many designs of stone column are based on the unit cell concept. However, the intrinsic mechanism of stress transfer between the column and the surrounding soil has not been investigated thoroughly. This paper presents the important features of stress sharing mechanism in unit cell concept under an embankment loading. The arching effect, the deformation mode, the stress concentration ratio and the plastic straining in the unit cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…At the same tank load value, the 3D modelling implied settlement and internal forces of raft foundation on the unsaturated soil smaller than those of the 2D modelling as an evidence of the higher bearing capacity determined by 3D modelling. The later results match well with the studies of [51,53]. The settlement and the internal forces were calculated approach the failure of the saturated soil for both the 2D and 3D simulations.…”
Section: Discussionsupporting
confidence: 87%
“…At the same tank load value, the 3D modelling implied settlement and internal forces of raft foundation on the unsaturated soil smaller than those of the 2D modelling as an evidence of the higher bearing capacity determined by 3D modelling. The later results match well with the studies of [51,53]. The settlement and the internal forces were calculated approach the failure of the saturated soil for both the 2D and 3D simulations.…”
Section: Discussionsupporting
confidence: 87%
“…This model is mostly used to compute realistic bearing capacity and collapse loads of footing as well as other application in which the failure behaviour of soil plays dominant role. Ng and Tan [42] stated that stone column in the unit cell shared about 4-5 times more loads than the surrounding soils throughout the column depth. They concluded that PLAXIS 2D and 3D models give results that are similar to each other especially on the settlement performance and the failure mechanism.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Therefore shape of unit cell does not affect the vertical load intensity-settlement relationship. In Plaxis 3D model, intrinsic mechanism such as the continuous shearing plane that occurred in the granular pile cannot be reproduced correctly by the axisymmetrical model [42]. Due to geometry limitation in PLAXIS, the cylindrical unit cell of equivalent diameter was simulated as square unit cell model in the present study.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Theoretically, the unit cell model is mostly used to analyse granular columns (Castro, 2017). It consists of a single column and its corresponding tributary area transformed into an equivalent circle (influence zone) with the same cross-sectional area (Ng & Tan, 2015). The diameter of a unit cell is equal to de = 1.05 -1.13s for triangular and square grids, respectively, where s is the centre-to-centre spacing between columns (Castro, 2017).…”
Section: Introductionmentioning
confidence: 99%